Influence of Dividend Policy on Stock Price of Nepalese Development Banks (People's Journal of Management, 2025)
This study aims to understand the relationship between dividend policies and changes in stock prices by investigating the impact of dividend announcements on the stock prices of development banks in Nepal. Using secondary data collected from all sixteen of Nepal's development banks between 2014 and 2023, the study draws conclusions using a descriptive and analytical research design. This research examines the relationships between the dependent variable Stock Price (SP) and independent variables such as Dividend Per Share (DPS), Dividend Yield (DY) and Dividend Payout Ratio (DP Ratio) using correlation and regression analysis. The reliability of the data is shown by several diagnostic tests that validate both the accuracy and the extent of the regression. The findings demonstrate a positive and significant impact of dividend payout ratios (DP Ratios) and dividends per share (DPS) on stock prices. As a result, the dividend payout ratios frequently increase in correlation with the SP. In contrast, high dividend yields could be seen as a sign of lower stock price (SP) or more risk, considering DY's significantly negative impact on SP. All indications and bird-in-hand hypotheses put dividend policy's effect on investor sentiment and stock prices to rest. Management may be able to gain the trust of investors and give them more agency if dividends are retained.